Effect of a 25 ingredient sport drink on exercise performance and muscle oxygen extraction: a randomized controlled cross-over trial - Gatterer, H.; Philippe, M.; Fröhlich, H.; Bachler, S.; Mosbach, F.; Burtscher, M. (Current Issues in Sport Science, 2017)
Many sport drinks contain a mixture of potential ergogenic substances. Recently, a new sport drink with 25 different ingredients was introduced to the market. Various athletes reported beneficial performance effects from the supplement, though without scientific evidence. The aim of this study was to investigate the effects of the sport drink on exercise performance. Nine sport students performed 3 test sessions including a cycle exercise tests to exhaustion, a leg strength test and a jump test. Each session was separated by 1 week. The first session was performed as a familiarization trial. In a random order, half of the participants performed the second session after consumption of the multi ingredient sport drink (MISD intake of 40g, 24 and 1h before each test) and half after placebo ingestion (same amount). During test session 3 the conditions were reversed (cross-over setting). Near infrared spectroscopy analyses were performed on the vastus lateralis during the MISD and placebo cycling test. The sport drink compared to placebo, improved maximal power output (7 watts, 95% CI 1.1-13.4), increased maximal lactate concentration (2.5 mmol/l, 95% CI 1.6-3.4), and power output at the individual threshold (Dmax) (6.1 watts, 95% CI 1.9-10.3). Power output at the 4 mmol/l threshold was reduced (9.0 watts, 95% CI -17.4 to -0.6) during the MISD trial. Additionally, the sport drink led to a steeper tissue oxygenation index decrease (TOI, slope: -0.0182±0.0084 vs. -0.0256±0.0073, p<0.005) during the test. Leg strength and jump ability was not affected by the supplement. The sport drink slightly increased power output during an incremental exercise test. Due to the broad range of substances in the supplement and their different effects, the factors involved in the performance enhancement are speculative. Data show that factors other than muscle oxygen extraction (represented by TOI) are involved in the improved maximal power output.